2022
DOI: 10.1136/tsaco-2021-000800
|View full text |Cite
|
Sign up to set email alerts
|

Patient and clinician perceptions of the trauma and acute care surgery hospitalization discharge transition of care: a qualitative study

Abstract: ObjectivesTrauma and acute care surgery (TACS) patients face complex barriers associated with hospitalization discharge that hinder successful recovery. We sought to better understand the challenges in the discharge transition of care, which might suggest interventions that would optimize it.MethodsWe conducted a qualitative study of patient and clinician perceptions about the hospital discharge process at an urban level 1 trauma center. We performed semi-structured interviews that we recorded, transcribed, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 37 publications
0
5
0
4
Order By: Relevance
“…The pilot study also introduced a new trauma APP role. Previous research has shown that when trauma APPs are incorporated into the trauma team and entrusted with managing the multidisciplinary discharge planning process, they can interact with patients and families, serve as the main liaison and advocate for nursing-related concerns, and provide leadership, mentorship, and teaching to bedside nurses caring for trauma patients (Collins et al, 2014;Crawford, 2019;McFadden et al, 2022). In a study of Medicare beneficiaries, Meddings et al (2023) found that patients who had an APP involved in their care had a reduced risk of readmission to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The pilot study also introduced a new trauma APP role. Previous research has shown that when trauma APPs are incorporated into the trauma team and entrusted with managing the multidisciplinary discharge planning process, they can interact with patients and families, serve as the main liaison and advocate for nursing-related concerns, and provide leadership, mentorship, and teaching to bedside nurses caring for trauma patients (Collins et al, 2014;Crawford, 2019;McFadden et al, 2022). In a study of Medicare beneficiaries, Meddings et al (2023) found that patients who had an APP involved in their care had a reduced risk of readmission to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The data from this study showed that the most significant increases in the care competence occurred after the guidelines and training provided in the hospital environment and at the end of followup in the Intervention Group. It is known that the educational strategies aimed at instrumentalizing informal caregivers described in the literature were successful 4,[7][8]12,21 . However, the results of this clinical trial, supported by data from the pilot study 5 , reinforce that providing health guidelines only in the hospital without proper monitoring at home is not sufficient to sustain the caregivers' competence after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…An initial and ongoing assessment of the dyad is essential for planning and implementing strategies to support clients and their family [22][23] and, thus, promote care continuity. Such moment provides time and support for discharge planning, anticipating conditions that may occur at home, enabling those involved to deal with the functional decline of their family members, in addition to determining the caregiver's psychological readiness to promote active involvement in decision-making and ease the education required for health self-management 12,23 . Secondly, in the home environment, the interventions should be based on experiences and difficulties adapting to the role of caregiver 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations